Physical and SPF Value Stability Studies Avocado Oil Nano-emulgel with Carbopol 980 as A Gel Base - Ayu Shabrina; Diva Ma'arif Pangestu; Siska Amaliyah; Malinda Prihantini; Junvidya Heroweti; Listyana Dewi Prastiwi (JPSCR: Journal of Pharmaceutical Science and Clinical Research, 2025)
Avocado oil (AVO) is a natural source of many unsaturated fatty acids that can help protect the skin from harmful UV radiation. The high content of unsaturated fatty acids in avocado oil can affect product stability. One way to overcome the stability of avocado oil for topical preparation is by formulating it into a gel base using Carbopol 980. The purpose of this study was to determine the physical stability and SPF value of avocado oil nano-emulgel (NE) with variations of Carbopol 980 as a gel base for 28 days of storage. AVONE was made with 5% AVO and Carbopol 980 base variation of 0.5% (NE1), 1.0% (NE2;), and 1.5% (NE3.) AVONE was stored in a climatic chamber at 30° ± 2°C with RH 65% ± 5%. The samples were tested for physical and SPF values before storage on days 7, 14, 21, and 28. The data obtained were analyzed statistically using one-way Anova. The AVONE on organoleptic parameters were stable; the resulting colour is broken-white with a distinctive oil aroma and thick and homogeneous texture. The pH value ranged from 6.21 ± 0.02 - 7.21 ± 0.02, with all formulas stable during storage. The viscosity value ranged from 13.28±0.23 - 47.22±0.89 dPa.s; the viscosity of NE3 was stable during storage. Adhesion and spreadability showed good ability to adhere to the skin. The SPF values ranged from 8.95±0.43 – 22.41±0.21, and NE3 was stable during storage. Avocado oil nano-emulgel with Carbopol 980 concentration of 1.5% was stable during storage.